OP0118 Development of metabolic syndrome in patients with sle: results from an inception cohort. (12th June 2018) - Mohammed, A.; Jefferies, M.; Pemberton, P.; Lunt, M.; Parker, B.; Bruce, I.N.; ,
Abstract : Background: Individuals with systemic lupus erythematosus (SLE) are at increased risk of cardiovascular disease, which is possibly related to metabolic syndrome (MetS). Previous studies suggest that inflammation may be an important underlying mechanism in MetS development, but include patients with prevalent MetS only. In order to assess whether the development of incident MetS could be predicted, we examined the association between the onset of MetS and disease activity, therapeutic exposure, and biomarkers of inflammation overtime in patients with SLE. Objectives: 1) To identify the clinical characteristics of patients with recently diagnosed SLE who develop incident MetS during first two years of follow-up; 2) To determine whether metabolic and inflammatory biomarkers improve the ability to predict incident MetS during follow-up. Methods: We studied 1687 recently diagnosed SLE patients (<15 months) enrolled into the SLICC Inception Cohort from 11 countries. Clinical, therapeutic and laboratory data were recorded at baseline and annually at follow-up visits. Serum concentrations of adiponectin, B-lymphocyte stimulator, high sensitivity C-reactive protein, interleukin (IL)−6, IL-18, IL-18 binding protein, insulin, leptin and tumour necrosis factor alpha were measured, if samples were available. A complete-case analysis was performed. Only patients with both MetS status available at baseline, year 1 and year 2 visits were analysed. Logistic regression was performed to analyse which factors were predictive of the development of incident MetS in the first 2 years of follow-up. Patients who developed incident MetS were compared with those who were free of MetS throughout follow-up. Results: Overall, 436 (26%) patients were included in this complete-case analysis. Of these, 243 (56%) were free of MetS throughout the follow-up period, 87 (20%) had persistent MetS at each visit, and 106 (24%) developed incident MetS during follow-up. In a multivariable logistic regression model that excluded biomarkers, clinical factors associated with future onset of MetS included increased age, Hispanic ethnicity, active renal disease, higher disease activity and current corticosteroid use. This model performed 'fairly' when identifying patients likely to develop incident MetS (Area Under Receiver Operator Characteristics Curve (AUC ROC)=0.77). In a multivariable model that included the inflammatory and metabolic biomarkers, increasing age, Korean ethnicity, higher disease activity and increased serum leptin performed similarly (AUC ROC=0.75). Conclusions: SLE patients who develop incident MetS exhibit a more inflammatory disease phenotype, with higher corticosteroid exposure in the preceding visit. Increased serum leptin concentration is independently associated with future onset of MetS. These factors can help predict those at increased risk of developing future MetS and may help target patients for more focused cardiovascular disease prevention. Disclosure of Interest: None declared